2009
DOI: 10.1007/s00484-009-0223-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different periods of exposure to hot environment on rumen function and diet digestibility in sheep

Abstract: Effects of different periods of exposure to hot environments on rumen function, diet digestibility and digesta passage rate were studied in four adult not-pregnant Sardinian ewes housed in a climatic chamber. The ewes were kept in individual metabolic cages. The trial lasted 83 days; 17 days were spent under thermal comfort conditions (TC) [temperature-humidity index (THI) = 65.0 +/- 2.0], followed by 49 days under elevated THI (ETHI: THI = 82.0 +/- 2.5) and 17 days under thermal comfort (TC; THI = 65.0 +/- 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
60
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 26 publications
6
60
0
3
Order By: Relevance
“…Protein digestibility coefficients were similar at different temperatures in our study. Similar findings were also reported by Bernabucci et al (2009).…”
Section: Results and Disussonsupporting
confidence: 92%
See 1 more Smart Citation
“…Protein digestibility coefficients were similar at different temperatures in our study. Similar findings were also reported by Bernabucci et al (2009).…”
Section: Results and Disussonsupporting
confidence: 92%
“…Bernabucci et al (1999) reported an improvement of diet digestibility during a short time exposure of Holstein heifers to hot conditions, and found that when the exposure was prolonged, the diet digestibility was reduced. Digestibility coefficients of DM, OM, NDF, and ADF in sheep were not affected by short exposure (10 days) but were lower (p<0.01) after prolonged exposure to heat (Bernabucci et al, 2009). Protein digestibility coefficients were similar at different temperatures in our study.…”
Section: Results and Disussonmentioning
confidence: 87%
“…Similar data were reported in goat kids and in lambs by Piccione et al (2011Piccione et al ( , 2013. These findings may be related to the increase of some proteins, especially complement proteins, from this fraction which like the acute phase proteins are involved in the environmental stress response (Bernabucci et al 2009). …”
Section: Discussionsupporting
confidence: 79%
“…Similarly, higher concentrations of β 1 -globulins were found by Piccione et al (2011) in goat kids after birth. This is because the most important proteins included in β 1 -globulin fraction are the complement, which like the acute phase proteins are involved in the environmental stress response (Bernabucci et al 2009). On the other hand, Thomas (2000) stated that higher concentrations of β 1 -globulins in young calves may be a result of suckling.…”
Section: Discussionmentioning
confidence: 99%